2022
DOI: 10.3389/fonc.2022.880144
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Risk Factors and Incidence of Interstitial Pneumonia With CHOP-Like Regimens for Non-Hodgkin Lymphoma

Abstract: ObjectivesInterstitial pneumonitis (IP), a potentially fatal complication of non-Hodgkin Lymphoma (NHL) patients received CHOP (cyclophosphamide and doxorubicin and vincristine and prednisone)-like chemotherapy, negatively affected patients’ clinical outcome and quality of life. We aimed to explore patient-related, disease-related and drug-related risk factors associated with IP and gain a better understanding of the incidence in NHL patients.MethodsDatabases, including PubMed, Ovid, China National Knowledge I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Literature reports have shown that rituximab can cause IP. Wang Qian et al., 3 statistics showed that the incidence of IP in the R-CHOP group was 14.8%, which was significantly higher than the 2.4% incidence in the CHOP group. Other studies have also reported incidences ranging from 3.7% to 16.7%.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Literature reports have shown that rituximab can cause IP. Wang Qian et al., 3 statistics showed that the incidence of IP in the R-CHOP group was 14.8%, which was significantly higher than the 2.4% incidence in the CHOP group. Other studies have also reported incidences ranging from 3.7% to 16.7%.…”
Section: Discussionmentioning
confidence: 97%
“…2 The reported incidence of IP in various studies varies greatly, ranging from 0.03% to 29.0%. 2 , 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations